From awareness to action: Social valuation of climate change mitigation options in Kenyan dairy farming - Florez Herrera, Jesus Fernando; Burkart, Stefan (2025)
In Kenya, where small-scale dairy farming is a vital part of the economy, farmers face increasing challenges from rising temperatures, changing rainfall patterns and degraded pastures. These climate risks affect productivity, making it crucial for farmers to adopt strategies that mitigate these effects. A recent study conducted by the CGIAR Initiative Livestock & Climate (L&C) has provided a closer look at how Kenyan dairy farmers perceive and are prepared to adopt climate change mitigation strategies.